HISTÉRICAS, ORDINÁRIAS E LOUCAS: O EROTISMO CONSERVADOR DAS PORNOCHANCHADAS - Julia Dias Alimonda (TRF2, 2019)
This article aims to analyze the eroticism and the representation of femininity in pornochanchada, the most popular genre in the history of national cinema. During the conservative military dictatorship, erotization dominated the screens of the whole world, arriving at Brazil in the form of pornochanchada. Those films overcame censorship and presented sexual discourses highly indecent to the moral values of the time, but, because they did not present explicit criticisms to the policy of the military dictatorship, the genre was considered alienating and futile, showing the disregard of the critics for the cinema of the masses and for sexual discourses. It's clear that the eroticization displayed on the screen was conservative, as female stereotypes perpetuated gender roles in order to please the desires of the male audience.